Insurance market maturity: A comparative study in Poland and Lithuania - Bernat, Tomasz; Grundey, Dainora (Technological and Economic Development of Economy, 2007)
Market economy, functioning in most countries of the world, is built of markets operating within it. Overviewing its origin historically, we should analyse the stages of its development or transformations, which influenced its present form. The markets in the economies are more or less free and the economies are more or less market, depending on the state's policy, the citizens’ attitudes, the legal system etc [1, p. 19–20]. These factors form the functioning of individual markets with all the elements of their effects. The aim of the paper is the analysis of insurance markets in Poland and Lithuania in reference to EU‐15. It is subordinated to a research hypothesis, which states that insurance markets of the surveyed countries (Poland and Lithuania), which have experienced system transformations, are further formed according to the model of the developed‐mature markets, which are functioning in market economies for many years.Draudimo rinkos branda: lyginamoji Lenkijos ir Lietuvos analizėSantrauka. Straipsnyje nagrinėjama draudimo rinkos tematika, ypač aktualūs reiškiniai šiai rinkai pasiekus brandos stadiją. Autoriai akcentuoja, jog išsivysčiusiose pasaulio šalyse rinkos ekonomika – jau seniai vyraujantis rinkos svertas. Tačiau naujosios Europos Sąjungos (ES) šalys, įskaitant Lenkiją ir Lietuvą, perėjo daugelį rinkos transformacijų etapų, siekdamos įgyvendinti rinkos ekonomikos principus ir drąsiai žvelgdamos į savo „eksperimentų“ rezultatus. Šio straipsnio tikslas – Lenkijos ir Lietuvos draudimo rinkų situacijos vertinimas ES-15 šalių kontekste. Straipsnyje pagrindžiama hipotezė, jog tirtose šalyse (Lenkijoje ir Lietuvoje), kurios perėjo ekonomikos sistemos transformacijas, draudimo rinkos funkcionavimas modeliuojamas pagal išsivysčiusių šalių modelius, kurie jau seniai jose funkcionuoja ir yra ekonomiškai naudingi.Reikšminiai žodžiai: draudimo rinka, rinkos branda, konkurencija, Lenkija, Lietuva.First Published Online: 21 Oct 2010